Social protection for Mozambique's elderly: History, structure, and potential effectiveness - Sara Almeida; Hanna Berkel; Sam Jones; Patricia Justino; Telça Massingue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This study assesses the effectiveness of Mozambique's flagship social pension programme, the elderly component of the Programa de Subsídio Social Básico (PSSB). Focusing on three key criteria- programme targeting, reliability, and materiality-we combine administrative data on the universe of beneficiaries with the complete records of the 2017 Population and Housing Census. Merging these datasets at the localidade level, we provide a highly granular view of programme coverage rates and payment delivery regularity. We estimate that in the best case with zero targeting errors, the PSSB-Elderly programme reaches two-thirds of its target group. However, significant regional disparities persist, including undercoverage in poorer regions. Additionally, we document substantial delays in payments since 2023, as well as various inaccuracies in the beneficiary registry. These findings underscore the importance of simple and robust designs for social protection in resource-constrained contexts. They also suggest that expanding programme coverage towards a quasi-universal subsidy in high-poverty locations merits serious consideration.
Keywords: H55; I38; E61; 330; social pensions; programme targeting; coverage gaps; payment delays; Mozambique